Family Resilience dalam Perspektif Al-Qur’an sebagai Upaya Meminimalisir Kasus Broken Home - Muh. Mukmin Passa; Pratiwi; Arjuna; Patma (Yayasan Al-Afif, 2025)
The issue of weakening family resilience, characterized by an increase in domestic conflicts and broken homes, has become a serious challenge in the social life of Muslim communities. This article aims to examine and analyze the concept of family resilience from the perspective of the Qur'an and its relevance as an effort to minimize broken homes. This study uses a qualitative method with a library research approach. Data were collected through a search of Qur'anic verses related to family, marriage, children, and property, and analyzed using a thematic (maudhu'i) approach through references to tafsir books and relevant scientific literature. The results show that the Qur'an views family resilience holistically, covering spiritual, emotional, moral, and social dimensions. Property and children are positioned as tests (fitnah) that can strengthen or weaken the family, depending on how they are managed. The actualization of the values of sakinah, mawaddah, rahmah, positive parenting, effective communication, and early detection of crises has been proven to play a strategic role in preventing broken homes. This study concludes that the Qur'an offers a relevant conceptual and practical framework for building resilient and sustainable Muslim families.